Bone protection by inhibition of microRNA-182. Issue 1 (December 2018) - Inoue, Kazuki; Deng, Zhonghao; Chen, Yufan; Giannopoulou, Eugenia; Xu, Ren; Gong, Shiaoching; Greenblatt, Matthew; Mangala, Lingegowda; Lopez-Berestein, Gabriel; Kirsch, David; Sood, Anil; Zhao, Liang; et al.
Abstract Targeting microRNAs recently shows significant therapeutic promise; however, such progress is underdeveloped in treatment of skeletal diseases with osteolysis, such as osteoporosis and rheumatoid arthritis (RA). Here,  we identified miR-182 as a key osteoclastogenic regulator in bone homeostasis and diseases. Myeloid-specific deletion of miR-182 protects mice against excessive osteoclastogenesis and bone resorption in disease models of ovariectomy-induced osteoporosis and inflammatory arthritis. Pharmacological treatment of these diseases with miR-182 inhibitors completely suppresses pathologic bone erosion. Mechanistically, we identify protein kinase double-stranded RNA-dependent (PKR) as a new and essential miR-182 target that is a novel inhibitor of osteoclastogenesis via regulation of the endogenous interferon (IFN)-β-mediated autocrine feedback loop. The expression levels of miR-182, PKR, and IFN-β are altered in RA and are significantly correlated with the osteoclastogenic capacity of RA monocytes. Our findings reveal a previously unrecognized regulatory network mediated by miR-182-PKR-IFN-β axis in osteoclastogenesis, and highlight the therapeutic implications of miR-182 inhibition in osteoprotection. Osteoclasts mediate bone disruption in a number of degenerative bone diseases. Here, the authors show that miR-182 regulates osteoclastogenesis via PKR and IFN-beta signaling, is correlated with rheumatoid arthritis, and that its ablation or inhibition is protective against bone erosion in mouse models of osteoporosis or inflammatory arthritis.